ISOLASI, PURIFIKASI DAN KARAKTERISASI Î±-AMILASE DARI Trichoderma viride FNCC 6013 - Atmaja, Dwi Surya (Chem Info Journal, 2013)
Isolation, purification and characterization of Î±-amylase from Tichoderma viride FNCC 6013 were doing to get an Î±-amylase from Tichoderma viride FNCC 6013, to get value of specific activity before and after purification by gel filtration and to know the characteristic this enzyme like time incubation, pH and optimum temperature. Alpha amylase is amylolytic enzyme that hydrolysis soluble starch to produce simple sugar like maltose. Alpha amylase was isolated continued with first purification using ammonium sulphate and chromatograph gel filtration. The measured specific activity of Î±-amylase after purified by gel filtration show increased 381.91% more than before purified by gel filtration whereas specific activity before and after purification by gel filtration is 1.631 Unit/mg protein and 7.860 Unit/mg protein. The characteristic of Î±-amylase show that optimum time incubation is 28 minute, value of optimum pH is 4.7 and optimum temperature is 28 0C.